Mechanism of Negative Emotions of the Elderly in Normalization Period of COVID-19: A Mediated Mediation Model - Xu, Kai (Frontiers in Public Health, 2022)
To explore the mechanism of negative emotions of the elderly in normalization period of COVID-19. The self-rating Depression Anxiety Stress Scale, epidemic attention scale, subjective economic status scale and physical health perception scale were used to investigate 318 elderly people in 2021. There were significant differences in negative emotions among the elderly in Henan in China with different gender, education background, medical insurance and whether they contacted suspected cases (all P < 0.05), but there was no significant difference on religious belief (P > 0.05); Attention to epidemic information was positively correlated with negative emotion (r = 0.492, P < 0.01), and negatively correlated with subjective economic status (r = −0.138, P < 0.05); Negative emotions were negatively correlated with subjective economic status (r = −0.455, P < 0.01) and health perception (r = −0.277, P < 0.01); health perception was no significant correlation with epidemic attention(r = −0.047, P > 0.05) and subjective economic status (r = −0.033, P > 0.05). Bootstrap test found that epidemic attention can significantly predict negative emotion of the elderly (β = 0.492, P < 0.001), subjective economic status played a partial mediating role between epidemic attention and negative emotions (β = 0.438, −0.395, P < 0.001), and health perception moderated the first half of the mediating path (β = 0.403, P < 0.001, 95% CI = [0.286 0.521]). Epidemic attention has a significant positive impact on the negative emotions of the elderly in Henan during normalization period of COVID-19, and it has effect indirectly through subjective economic status; health perception plays a moderator role in the impact of epidemic attention on subjective economic status.